The Impact of Online Collaborative Writing Activities on English Language Learners' Writing Skills at the Faculty of Teacher Training and Education, Lancang Kuning University - Hutabarat, Pebri Yuni Br; Herlinawati , Herlinawati (Jurnal Biochamp, 2025)
Online Collaborative Writing Activities strategy in the writing learning process provides more opportunities for students to be more active in the learning process. This is because collaborative activities offer significant benefits for students, especially in the learning process at the English Department Universitas Lancang Kuning. This thesis discusses the effects of online collaborative writing activities in the fifth semester of the English Department at Universitas Lancang Kuning. The purpose of the research is to find out the impact of using online collaborative writing activities on writing ability. The method of this research was experimental research with Quasi-Experimental design. This research was conducted from December 2021 to January 2022. The instruments used in this research were tests to write argumentative essays. The results of this research on the effects of using online collaborative activities in EFL writing students' are higher in using group rather than pair activities. This is evidenced by the mean difference between the group and pair activity classes, which is 88.55 > 84.89. Based on the results of Ngain's mean value, it can be concluded that online collaborative writing activities are less effective (40-55%). In addition, there is a significant difference between the group activity class and the pair activity class